Application of canonical analysis to air temperature and precipitation regimes over Greece - Nastos, P.Th.; Philandras, C. M.; Repapis, C. C. (Fresenius Environmental Bulletin, 2002)
The goal of this study is to estimate the relation between air temperature and precipitation in Greece and, thereafter, to define the regions of the covariability of the two parameters. For that purpose, the air temperature and precipitation mean monthly data of 30 meteorological stations, for the period 1950-2000, are analyzed. The first step is the application of Factor Analysis (FA) to each of the two variable groups of the seasonal air temperature and precipitation. The aim is to reduce the number of variables in each group and, more specific, to define the main significant factors for each parameter. The second step is the application of Canonical Correlation Analysis (CCA) to the factor scores of each parameter, derived by the use of PCA, so that the canonical pairs are extracted and the number of the pairs are equal to the minimum number of variables in either set. In the process, the computed canonical scores are correlated to the respective original data, aiming to define regions of positive and negative correlations between the canonical roots of the air temperature and precipitation.
Keywords: air temperature; canonical analysis; Factor analysis; Greece; precipitation (climatology)